Corporate value and trade-credit policies: Evidence from China - Umeair Shahzad; Lingge Zhao; Jing Liu; Fukai Luo (Journal of Applied Economics, 2022)
This study evaluates the nexus ofenterprise value and trade-credit strategies. Fixed-effects modeling is used for the baseline outcomes, and a difference-in-difference approach is applied as a quasi-natural experiment. The estimates are robust to alternative measures and distant covariates. The findings validate that enterprise value has a positive (negative) impact on trade-credit (supplies), (demand). The said effect is more pronounced in SOEs, revealinga critical role in capital mobilization. The additional analyses show that financially constrained and equity reliant firms are more likely to exploit firm value in trade-credit management. The micro aspect of this study suggests that enterprise value can allow managers to shape non-price competitive strategies and it also offers incentives to maintain financial slack. On a macro level, the studysuggests that enterprise value has a critical role in capital mobilization and enhancing the purchasing power in the overall economy.
Keywords: 330; equity financing; financial flexibility; Firm value; trade-credit policies